Inovasi Pendidikan, Jenis-Jenis Tenaga Kependidikan dan Bentuk Inovasi Pendidikan dalam Bidang Tenaga Kependidikan - Mita Haryati; Fajri Ismail; Muhammad Win Afgani (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Innovation in education has become a key factor in improving the quality of human resources in the era of globalization. Educational personnel, as an important element in the education system, play a strategic role in creating an effective and adaptive learning environment in response to technological developments. However, various challenges are still faced in efforts to improve the quality of educational staff in Indonesia, including the lack of continuous training, low utilization of technology in learning, and limited policies supporting the welfare of educational staff. This research uses a literature study method with a content analysis approach on various academic literature relevant to educational innovations in the field of educational personnel. The study results show that innovation in education, particularly in the field of educational personnel, includes the development of competencies through continuous training, the utilization of information technology in learning, and policy reforms that support the welfare and professionalism of educational personnel. Moreover, the application of digital technology in the learning process can enhance teaching effectiveness and student engagement. The implications of this research emphasize the importance of collaboration between the government, educational institutions, and society in creating an innovative and sustainable education system. Investment in the development of quality educational personnel is expected to enhance the competitiveness of national education and produce graduates who are ready to face global challenges. Therefore, a comprehensive and sustainable strategy is needed to ensure that educational staff possess competencies that meet the demands of the times. Keywords: Educational innovation, educational staff